Investigating Pore‐Opening of Hydrogel Foams at the Scale of Freestanding Thin Films. Issue 17 (6th September 2022) - Andrieux, Sébastien; Patil, Mayur; Jacomine, Leandro; Hourlier‐Fargette, Aurélie; Heitkam, Sascha; Drenckhan, Wiebke
Abstract : Back Cover : In article number 2200189 by Sébastien Andrieux, Wiebke Drenckhan, and co‐authors, the evolution of gelling alginate thin films upon drying in a microfluidic thin film pressure balance is demonstrated. A tear appears and spreads as the thin film dries. Such an experiment could be the basis for an in‐depth investigation of the film rupture mechanisms responsible for pore‐opening in polymer foams.